2019
DOI: 10.5194/angeo-37-1005-2019
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of intermediate descending layers (or 150 km echoes) over the equatorial and low-latitude regions of Brazil during the deep solar minimum of 2009

Abstract: Abstract. In this work, we have performed a study for the first time on the climatology of the intermediate descending layers (ILs) over Brazilian equatorial and low-latitude regions during the extreme solar minimum period of 2009. The result of this study shows that the occurrence frequency of the ILs is very high, being > 60 % over São Luís (2∘ S, 44∘ W; inclination: −3.8∘) and > 90 % in Cachoeira Paulista (22.42∘ S, 45∘ W; inclination: −33.5∘). In most cases the ILs occur during the day at altitudes v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 44 publications
4
19
2
Order By: Relevance
“…While the radar registered ILs occurring simultaneously at different heights in the time intervals of ~13:00–14:00 LT, and ~16:30–17:00 LT, the Digisonde showed only one single layer in the time intervals of 15:35 LT to 16:35 LT and 17:20 LT to 18:10 LT. We can observe that the time intervals in which the ILs were observed in the radar were not coincident with the register from the Digisonde. As mentioned by Dos Santos et al (2019), simultaneous ILs were a common feature observed over SL, but during this specific day, they were not observed by the Digisonde as by the radar. Another point is that both the ILs from the Digisonde were formed from the detachment of the F1 layer.…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…While the radar registered ILs occurring simultaneously at different heights in the time intervals of ~13:00–14:00 LT, and ~16:30–17:00 LT, the Digisonde showed only one single layer in the time intervals of 15:35 LT to 16:35 LT and 17:20 LT to 18:10 LT. We can observe that the time intervals in which the ILs were observed in the radar were not coincident with the register from the Digisonde. As mentioned by Dos Santos et al (2019), simultaneous ILs were a common feature observed over SL, but during this specific day, they were not observed by the Digisonde as by the radar. Another point is that both the ILs from the Digisonde were formed from the detachment of the F1 layer.…”
Section: Resultssupporting
confidence: 52%
“…Journal of Geophysical Research: Space Physics observe that the time intervals in which the ILs were observed in the radar were not coincident with the register from the Digisonde. As mentioned by Dos Santos et al (2019), simultaneous ILs were a common feature observed over SL, but during this specific day, they were not observed by the Digisonde as by the radar. Another point is that both the ILs from the Digisonde were formed from the detachment of the F1 layer.…”
Section: 1029/2019ja027682mentioning
confidence: 52%
See 3 more Smart Citations